Rheumatoid factor and anticitrullinated protein antibodies in rheumatoid arthritis: diagnostic value, associations with radiological progression rate, and extra-articular manifestations. Issue 12 (16th November 2004) - De Rycke, L; Peene, I; Hoffman, I E A; Kruithof, E; Union, A; Meheus, L; Lebeer, K; Wyns, B; Vincent, C; Mielants, H; Boullart, L; Serre, G; et al.
Abstract : Background: Autoantibodies such as rheumatoid factor (RF) and anticitrullinated protein antibodies can be detected in rheumatoid arthritis (RA) sera. Objective: To determine the diagnostic values of RF, anticitrullinated protein antibodies, and the shared epitope (SE), and their associations with radiological progression rates and extra-articular manifestations. Methods: Population 1 consisted of sera from 315 patients, consecutively sent for detection of anticitrullinated protein antibodies, of which 264 were used to determine the sensitivity and specificity of RF and of antibodies against three synthetic citrullinated peptides: peptide A (pepA), peptide B (pepB), and CCP2. Population 2 consisted of sera from 180 longstanding RA patients and was used to determine associations of RA associated antibodies and the SE with radiological progression rates and extra-articular manifestations. Antibodies to pepA and pepB were detected by line immunoassay, and antibodies to CCP2 by ELISA. HLA Class II typing was performed by LiPA. Results: In population 1, we defined adapted cut offs corresponding to a specificity of ⩾98.5%. This yielded the following sensitivities: RF 12.8%; anti-pepA antibodies 63.6%; anti-pepB antibodies 54.2%; and anti-CCP2 antibodies 73.7%. In population 2, significant differences in radiological progression rates were found between positive and negative patients for different RA antibodies and the SE. RF, but not anticitrullinated protein antibodies or the SE, were more frequent in patients with extra-articular manifestations. Conclusion: A valid comparison of RA associated antibodies shows superior sensitivity of the anticitrullinated protein antibodies compared with RF. The presence of RA associated antibodies and the SE are indicative for poorer radiological outcome, and presence of extra-articular manifestations is associated with RF but not with anticitrullinated protein antibodies.